Factor that influence saving behaviour among household in Malaysia / Muhammad Faiz Jamaludin - Jamaludin, Muhammad Faiz (Faculty of Business and Management, 2018)
This project paper entitled “Factor That Influence Saving Behavior among Household in Malaysia” was conducted from September 2017 until January 2018. The researchers came out with this project paper to investigate the factor that influence saving behavior among household in Malaysia. The dependent variable of the study is saving while independent variables are interest rate, inflation rate, income level and consumption level. The study was conducted in Malaysia and used 37 observation of annually period of data which from 1980 until 2016. This study used time series data and also applied Multiple Linear Regression method in order to study the existence of relationship between those variables. The result of this study found that interest rate, inflation rate and consumption level has positive significant relationship with saving while income level do not have significant relationship with saving.